Capital Adequacy Ratio, Loan To Deposit Ratio Dan Non Performing Loan Terhadap Return On Equity Pada Perusahaan Perbankan - Tasya Umaira; Syahyunan Syahyunan; Teguh Setiawan (Pusat Riset Manajemen Dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia, 2022)
This study aims to determine the effect of capital adequacy ratio, loan to deposit ratio and non-performing loan on return on equity in banking companies listed on the Indonesia Stock Exchange. This research is causal associative research and the type of data used is quantitative data. The data used is obtained from the company's financial statements that have been audited on the Indonesia Stock Exchange during the study period. The analytical method used is descriptive analysis and multiple linear regression of panel data. The population of this study is banking companies for the 2016-2020 period, which totals 40 companies. The sample in this study amounted to 36 companies. The results of this study indicate that the capital adequacy ratio has a positive and insignificant effect on return on equity, loan to deposit ratio has a positive and insignificant effect on return on equity, non-performing loans have a negative and significant effect on return on equity. Capital adequacy ratio, loan to deposit ratio and non-performing loan simultaneously have a significant effect on return on equity.